Comparative in-vitro efficacy of fluoroquinolones against Streptococcus pneumoniae recovered from bacterial keratitis as determined by E-test - Ramakrishnan R; Ramesh S; Bharathi M; Amuthan M; Viswanathan S (Wolters Kluwer Medknow Publications, 2010)
Background and Objectives: The advent of new fluoroquinolones has drawn the attention for reliable methods on the in-vitro susceptibility testing of Streptococccus pneumoniae. This study attempts to determine the minimum inhibitory concentration (MIC) of second-generation (ciprofloxacin and ofloxacin), third-generation (levofloxacin) and the fourth-generation (moxifloxacin and gatifloxacin) fluoroquinolones against S. pneumoniae recovered from bacterial keratitis. Materials and Methods: In retrospect, the MICs of 50 strains of S. pneumoniae isolated from the corneal scrapes of patients with bacterial keratitis were determined against ciprofloxacin, ofloxacin, levofloxacin, gatifloxacin and moxifloxacin using E-tests. The National Committee of Clinical Laboratory Standards (NCCLS) susceptibility patterns and the potencies of the MICs were statistically compared. Results: The median MIC of ciprofloxacin (0.25μg/ml) was found to be lower than the median MICs of ofloxacin (0.5μg/ml) (P < 0.449) and levofloxacin (1.0μg/ml) (P < 0.001). The median MICs of gatifloxacin (0.1μg/ml) was lower than the median MICs of ciprofloxacin (0.25μg/ml) (P < 0.001), ofloxacin (0.5μg/ml) (P < 0.001) and levofloxacin (1.0μg/ml) (P < 0.001). Moxifloxacin (0.06μg/ml) had showed lower median MICs than gatifloxacin (0.1μg/ml) (P < 0.001) levofloxacin (1.0μg/ml) (P < 0.001), ofloxacin (0.5μg/ml) (P < 0.001) and ciprofloxacin (0.25μg/ml) (P < 0.001). Moxifloxacin (0.06μg/ml) had a lower MIC50 (μg/ml) than gatifloxacin (0.1μg/ml), levofloxacin (1.0μg/ml), ciprofloxacin (0.25μg/ml) and ofloxacin (0.5μg/ml). MIC90 (μg/ml) of moxifloxacin (0.06μg/ml) was found to be lower than the MIC90 (μg/ml) of gatifloxacin (0.5μg/ml), levofloxacin (1.0μg/ml), ofloxacin (0.5μg/ml) and ciprofloxacin (0.5μg/ml). Conclusion: Based on in-vitro testing, the five portrayed fluoroquinolones 100% sensitivity to S. pneumoniae. However, the fourth-generation fluoroquinolone, moxifloxacin appeared to be more effective against S. pneumoniae than gatifloxacin, levofloxacin, ofloxacin and ciprofloxacin.